I was curious as to what value $\displaystyle\sum_{n\in\mathbb{Z}\text{, }n\ge 2}\frac{(-1)^n}{\log(n)}$ converges to.

One person who commented on this post said that the sum could be written as an integral:

$\displaystyle\int_0^\infty\left(1-\left(1-2^{1-x}\right) \zeta\left(x\right)\right){\rm d}x$

where $\zeta\left(x\right)$ is the Riemann Zeta function.

How do you get from this sum to that integral? And is this indeed the correct integral representation for this particular sum?

  • 2
    $\begingroup$ HINT - $\frac{1}{\log(n)}=\int_0^{\infty } n^{-x} \, dx$ $\endgroup$ – Mariusz Iwaniuk Apr 11 '18 at 17:27
  • 2
    $\begingroup$ See this answer math.stackexchange.com/a/476526/61216 $\endgroup$ – gammatester Apr 11 '18 at 17:35
  • $\begingroup$ I believe it is simpler to write the wanted series just as $$\sum_{n\geq 2}\frac{(-1)^n}{\log n}.$$ $\endgroup$ – Jack D'Aurizio Apr 11 '18 at 17:55

For any $s\geq 1$ we have $$ \zeta(s)=\sum_{n\geq 1}\frac{1}{n^s},\qquad \eta(s)=\sum_{n\geq 1}\frac{(-1)^{n+1}}{n^s}=\left(1-\frac{2}{2^s}\right)\zeta(s) $$ but the series defining $\eta(s)$ is conditionally convergent for any $s>0$, allowing the analytic continuation $$ \forall s:\text{Re}(s)>0,\qquad \zeta(s)=\left(1-\frac{2}{2^s}\right)^{-1}\sum_{n\geq 1}\frac{(-1)^{n+1}}{n^s}=\left(1-\frac{2}{2^s}\right)^{-1}\frac{1}{\Gamma(s)}\int_{0}^{+\infty}\frac{t^{s-1}}{e^t+1}\,dt $$ On the other hand $\frac{1}{\log n}=\int_{0}^{+\infty}\frac{ds}{n^s}$ for any $n\geq 2$, hence $$ \sum_{n\geq 2}\frac{(-1)^{n}}{\log n}=\int_{0}^{+\infty}(\eta(s)-1)\,ds=\int_{0}^{+\infty}\int_{0}^{+\infty}\frac{t^{s-1}}{\Gamma(s)e^t(e^t+1)}\,dt\,ds $$ and by integration by parts $$ \sum_{n\geq 2}\frac{(-1)^{n}}{\log n}=\iint_{(0,+\infty)^2}\frac{t^s(2+e^{-t})}{\Gamma(s+1)(e^t+1)^2}\,dt\,ds $$ Now the numerical evaluation of the RHS ($\approx 0.9243$) is not difficult since most of the mass of the integral is concentrated near the origin. We may also notice that the "naive" approximation $$ \int_{0}^{+\infty}\frac{t^s}{\Gamma(s+1)}\,ds \approx -\frac{1}{2}+\sum_{n\geq 0}\frac{t^n}{n!}=e^t-\frac{1}{2} $$ leads to an accurate estimation: $$ \sum_{n\geq 2}\frac{(-1)^n}{\log n}\approx \int_{0}^{+\infty}\frac{(2+e^{-t})\left(-\tfrac{1}{2}+e^t\right)}{(e^t+1)^2}\,dt = \frac{1}{4}+\log 2 = 0.943124\ldots $$ and allows to prove that $\sum_{n\geq 2}\frac{(-1)^n}{\log n}< 1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.